Pengaruh Virgin Coconut Oil (VCO) terhadap Ruam Popok Batita - Ilma Aktisodyah Ersada; Siska Ningtyas Prabasari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Background: Diaper rash cases in Indonesia have a relatively high prevalence in Central Java Province. Using disposable diapers on infants can have a negative impact on the skin, using them for too long can cause the skin to become damp so that the infants skin experiences irritation or rashes. Diaper rash is the most common skin problem caused by inflammation in areas covered by diapers such as genitals, buttocks, and inner groin. Objective: This study aims to determine the effect of administration of virgin coconut oil (VCO) on diaper rash in infants. Method: This research used pre-experimental techniques with a group pre-test and post-test design. The sample for this research was 20 participants. Data analysis used Wilcoxon signed rank test to test the effect of VCO on diaper rash. Results: VCO administration had an effect on reducing rash scores with a p-value of 0.000 < 0.05, so H0 was rejected and Ha was accepted. Summary: This study concludes that administration of VCO is very effective in the treatment of diaper rash in infants.